A Negotiated Relationship: Nuances of "Whitened" Biracial Educator Identities. Issue 1 (2nd January 2021) - Stohry, Hannah R.; Aronson, Brittany A.
Abstract: In this article, we explore our desire to better understand the complexity of multi-ethnic/racial identities, positionality, and how this relates to solidarity building within educative spaces. In particular, we are interested in the relationship between whiteness and its nuanced complexity of identities influencing "whitened" identities. As two racially ambiguous women educators situated in the United States, we consider how to deconstruct the constraints of identity constructs that allow for an empowered hybridity of identities? Using our testimonios as entry points to understanding our collective pain and hopes of healing with the help of Critical Whiteness Studies, Multicrit, and Chicana feminism as theoretical and methodological frameworks, we reveal two themes of legitimacy and coming to consciousness to seek ways to come together in solidarity, and consider new ways of theorizing hybrid identities. We offer recommendations for educators and critical scholars of race.